Digital Barriers in Online Gaming: An Emerging Psychosocial Challenge Among Children and Adolescents in the Post-Pandemic Era - Uppal, Palak; Shukla, Vikesh; Sharma, Navneet (Journal of Research in Vocational Education, 2025)
Technology and media have become integral to the lives of children, from infancy to adolescent age. Children are beginning to use digital devices, such as tablets and smart phones, at a very young age, often engaging in activities like playing video games and using social media. The COVID-19 pandemic significantly disrupted children's lifestyles, introducing abrupt constraints such as school closures, which led to a substantial rise in screen time across all age groups. Internet gaming disorder (IGD) is defined as the persistent and recurrent use of the Internet to engage in games, often with other players, leading to clinically significant impairment or distress. Several studies reported a dramatic rise in the prevalence of Internet Gaming Disorder (IGD) during this post Covid-19 period. This review article addresses different dimensional approach with Homoeopathic remedies to promote digital wellness for infants, children and adolescents and to bring in control the increasing cases of IGD in post COVID-19 era.